1994
DOI: 10.1017/s0033291700027847
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric MRI measurements in bipolars compared with schizophrenics and healthy controls

Abstract: SynopsisTwenty-six patients with RDC bipolar disorder were compared with a previously reported group of 48 RDC schizophrenics and 34 healthy controls, using volumetric MRI measurements of cerebral, cortical and sulcal volumes. The bipolar group appeared no different from the controls, and both of these groups had significantly larger cerebral and cortical volumes than the schizophrenics. Our previous report of a significantly reduced cortical volume in the schizophrenic group, with a corresponding increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
3
10

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(111 citation statements)
references
References 54 publications
4
94
3
10
Order By: Relevance
“…24 Zipursky et al 48 similarly found global volume reduction in gray matter in first-episode psychotic patients but not in first-episode affective psychotic patients. Harvey et al 49 also reported a decrease in cortical volume in patients with schizophrenia but not in patients with bipolar disorder. Since we have not investigated frontal or parietal cortex, 2 other areas possibly implicated in schizophrenic and affective pathology, 1,2 conclusions drawn herein about specificity apply only to the regions we have studied.…”
Section: Musiek and Reevesmentioning
confidence: 97%
“…24 Zipursky et al 48 similarly found global volume reduction in gray matter in first-episode psychotic patients but not in first-episode affective psychotic patients. Harvey et al 49 also reported a decrease in cortical volume in patients with schizophrenia but not in patients with bipolar disorder. Since we have not investigated frontal or parietal cortex, 2 other areas possibly implicated in schizophrenic and affective pathology, 1,2 conclusions drawn herein about specificity apply only to the regions we have studied.…”
Section: Musiek and Reevesmentioning
confidence: 97%
“…Other researchers such as Manjunath (2002a), and Hwang et al indicated cranial capacity in Indian, Korean male populations. Also Harvey et al (1994) showed that 41 Africans and West Indians had a smaller average brain volume than that of 67 Caucasians.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding overall sylvian fissure and sulcal changes, these results confirm previous findings using samples of schizophrenic patients unselected for familial forms of the illness. 13 In one study of adult offspring of schizophrenic women ('high-risk' individuals), overall brain sulcal CSF was increased in subjects with schizophrenia and in those with schizophrenia spectrum conditions, compared with unaffected but at-risk subjects. 15 The present finding of increased sylvian fissure volume in schizophrenic/schizoaffective subjects, as well as subjects with schizophrenia spectrum conditions or obligate carriers, supports the relationship between genetic risk for schizophrenia and sulcal enlargement.…”
Section: Discussionmentioning
confidence: 99%